Tingkat Kemampuan Literasi Informasi Mahasiswa UIN Raden Fatah Palembang Fakultas Adab Dan Humaniora Tahun 2020-2021 - Liiska, Erix Lia; Herlina, Herlina; Dalilan, Dalilan (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
Current technological developments require us to be able to search for information well. This research examines the information literacy ability of students. This research aims to determine the level of information literacy skills of students at UIN Raden Fatah Palembang, Faculty of Culture and Humanities in 2020-2021. This type of research is descriptive using a quantitative approach. Documentation and questionnaires were data collection techniques. Validity and reliability were tested using the Cronbach's Alpha technique with the help of IBM SPSS 23. The sampling technique used in this research was probability sampling limited by the Slovin formula, with a sample size of 217 students. The information literacy model used in this research is the Colorado information literacy guide model. The results of the study showed that, there are 9 indicators in the Colorado literacy guide model, namely determining information needs, information search strategies, obtaining information, analyzing information, processing information, organizing information, information action and evaluation. The research results also showed that the score values for all indicators calculated based on calculations using the Grand mean formula was in the interval 3.25-4.00. meaning that the level of information literacy skills of students at UIN Raden Fatah Palembang, Faculty of Adab and Humanities in 2020-2021 is in the very good category. In conclusion, students have the ability to search for information. Keywords : information literacy,level, ability